The Importance of Islamic Children's Education - Mohammad Rasikhul Islam (STAI Miftahul Ula Nganjuk, 2019)
Education is a process for human beings. Through human education it can grow and develop perfectly, thus fulfilling its duties and responsibilities as a human being. Education is capable of transforming people who were initially ignorant to know, bad to better, so important is education in Islam that it is an individual obligation to demand knowledge. The importance of early childhood education, demands an approach that will be used in learning activities that focus on the child. Because children are the breadwinner of every parent and the next generation of people, however, one of the problems that arises is that not every parent or educator is able to understand the right way to educate the child. Thus, in this article we will talk about educating children in order to create the next generation of potential future successors of the nation.